Development and characterisation of a humanised model of Parkinson's disease associated with delivery of adeno-associated virus expressing alpha-synuclein and pre-formed alpha-synuclein fibrils unilaterally into the rat substantia nigra - Burke, Teresa Ann (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2022)
Parkinson s disease (PD) is the most common motor neurodegenerative disease, characterised histologically by the presence of Lewy bodies, which are intracellular inclusions containing a variety of cellular proteins, the most abundant of which is a protein called alpha-synuclein. Autosomal dominant forms of PD can include N-terminal point mutations in alpha-synuclein such as A53T, as well as genomic duplications or triplications that contain the alpha-synuclein locus. The development of animal models associated with the over-expression of alpha-synuclein, including its mutated forms, are essential to gain insights into disease mechanisms and in drug development efforts which aim to slow the progression or cure the disease. This study aimed to develop and characterise a humanised model of PD associated with delivery of adeno-associated virus (AAV) expressing alpha synuclein and pre-formed alpha-synuclein fibrils (PFFs) unilaterally into the rat substantia nigra. Rats were unilaterally injected with a single injection of AAV5-CBA-alpha-synuclein wildtype (WT) human, AAV1/2-CMV-A53T human alpha-synuclein, PFF WT alpha-synuclein human, PFF A53T alpha-synuclein human, or two injections, one containing AAV and one containing PFF, into the substantia nigra and assessed at multiple time-points post-delivery for changes in motor behaviours in the stepping, cylinder, staircase and amphetamine rotation tests. Tyrosine hydroxylase (TH) immunoreactive cell loss was assessed through the use of TH immunohistochemistry to quantify dopamine neuronal cell loss. The presence of alpha-synuclein within the substantia nigra was verified by immunofluorescent staining of post-mortem tissue sections. The combination of AAV + PFF A53T injection into the male rat substantia nigra was found to be effective at stimulating motor deficits in the stepping test, with decreased contralateral stepping observed when compared with their ipsilateral stepping, as well as in the cylinder test, where increased ipsilateral wall contacts were observed when compared to all other treatment groups, and in the amphetamine test, where increased ipsilateral rotations were observed when compared to all other treatment groups. Furthermore neuronal cell loss, expressed as a percentage of the un-injected hemisphere, was observed in the substantia nigra of the PFF + AAV A53T treatment group when compared with PFF A53T alpha-synuclein treatment group at 6 weeks post-AAV + PFF delivery when all alpha-synuclein treated groups were compared. When the same treatment was given to female rats the development of motor behaviours in the stepping test occurred at 4.5 weeks post-AAV + PFF delivery, which is later than that observed in the male rats, at 3 weeks post-AAV delivery, indicating a less severe and/or more slowly progressive phenotype compared to males. Intranigral injection of AAV1/2-CMV-A53T human alpha-synuclein led to the loss of TH immunoreactive cells in the absence of a consistent motor deficit up to 13 weeks post-delivery, while intranigral injection of AAV5-CBA-alpha-synuclein WT did not lead to the development of motor deficits or TH immunoreactive cell loss up to 16 weeks post-delivery. The results of this research provide support for use of a combination of AAV + PFF mediated expression of A53T alpha-synuclein in the male rat substantia nigra as a preclinical model of synucleinopathy. The addition of the alpha-synuclein PFFs with the AAV alpha-synuclein is likely to lead to a greater accumulation of alpha-synuclein, potentially through the seeding of the PFFs and the recruitment of endogenous alpha-synuclein as a result. The development of a motor phenotype in addition to dopamine neuronal cell loss over a 6 week period lends well to the potential of the model for screening drug candidates which may slow the progression or protect against synuclein-induced neurodegeneration. However, this is a supraphysiological model of synuclein induced pathology and it remains to be confirmed that such a rapid induction of synuclein induced neurodegeneration bears a close resemblance to the human condition.
APPROVED